PENANAMAN NILAI-NILAI PANCASILA PADA EKSTRAKURIKULER KEROHANIAN ISLAM (ROHIS) DI SMAN 01 TELUK KERAMAT - Hazirawati Hazirawati; Sulistyarini Sulistyarini; Thomy Sastra Atmaja (Universitas Tanjungpura, 2022)
This study aims to determine the program, Pancasila values in the spiritual program, program implementation, and also the supporting and inhibiting factors in Kerohanian Islam (Rohis) extracurricular at SMAN 1 Teluk Keramat. The research method used is descriptive with a qualitative approach. The data sources for this research were the principal, supervisor, chairperson, and spiritual members. Data obtained through observation, interviews, and documentation. The results of this study indicate that the Pancasila values inculcation program includes several types of activities, including: religious activities, entrepreneurship, creativity and art, organizational, humanitarian/social, performance performance, and spiritual tourism. The Pancasila values that are instilled are divinity/religious values, humanity, unity, deliberation/democracy, and justice. The implementation of these programs is carried out in several places such as prayer rooms, classrooms, and outside the classroom with regular times every Friday or holidays. Some spiritual activities are in the form of controlling and improving the quality and quantity of worship (spiritual), and the other part is in the form of intellectual development and skill/creativity. The supporting and inhibiting factors for inculcating Pancasila values in spiritual extracurriculars are divided into two factors, namely internal and external factors.